Achieving more sustainable agricultural production: investigating the impact of agricultural machinery services on fertilizer reduction based on survey data from wheat farmers - Chenyang Liu; Wei Guo; Ling Xin (Frontiers in Sustainable Food Systems, 2025)
IntroductionReducing excessive fertilizer use is essential for mitigating environmental harm and achieving sustainable agricultural development. Agricultural machinery services (AMS) are considered a promising means to improve production efficiency and reduce the overuse of inputs. This study investigates the impact of AMS on fertilizer application intensity (FAI) among wheat farmers, aiming to understand whether and how AMS contribute to more sustainable fertilizer use.MethodsWe use survey data collected from 926 wheat farmers across five provinces in the North China Plain. To rigorously identify the effects of AMS on FAI, we employ a combination of linear regression, Least Absolute Shrinkage and Selection Operator (LASSO), two-stage least squares (2SLS), and mediation effect analysis to account for potential confounders and mechanisms.ResultsThe empirical analysis reveals three main findings: (1) AMS significantly reduce FAI, and the extent of reduction increases with higher levels of participation in AMS. (2) The FAI-reducing effect of AMS varies substantially across farmers with different socio-economic and farm characteristics. (3) Technological progress and changes in traditional fertilization practices are two key mediating mechanisms through which AMS lower FAI.DiscussionThese findings suggest that promoting AMS can effectively reduce FAI while supporting sustainable agricultural development. Policy efforts should focus on expanding AMS coverage and tailoring services to the needs of diverse farmer groups, thereby facilitating the transition of small-scale farmers toward modern, environmentally friendly production practices.